On the role of risk aversion and market design in capacity expansion planning - Christoph Fraunholz; Kim K. Miskiw; Emil Kraft; Wolf Fichtner; Christoph Weber (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2021)
Investment decisions in competitive power markets are based upon thorough profitability assessments. Thereby, investors typically show a high degree of risk aversion, which is the main argument for capacity mechanisms being implemented around the world. In order to investigate the interdependencies between investors' risk aversion and market design, we extend the agent-based electricity market model PowerACE to account for long-term uncertainties. This allows us to model capacity expansion planning from an agent perspective and with different risk preferences. The enhanced model is then applied in a multi-country case study of the European electricity market. Our results show that assuming risk-averse rather than risk-neutral investors leads to slightly reduced investments in dispatchable capacity, higher wholesale electricity prices, and reduced levels of resource adequacy. These effects are more pronounced in an energy-only market than under a capacity mechanism. Moreover, uncoordinated changes in market design may also lead to negative cross-border effects.
Keywords: 330; Agent-based simulation; Capacity expansion planning; Risk aversion; Electricity market design; Energy-only market; Capacity mechanism